The Role of Meaning in Life, Mindfulness and Resilience in the Flourishing of Students - M Nasiri; H Karsazi; F Esmaeilpour; M Beyrami (پژوهشنامه روانشناسی مثبت, 2015)
The purpose of the study was to evauate the role of meaning in life, mindfulness and resilience in the flourishing of students. Based on descriptive – analytic method, two hundred and forty students of Tabriz University were selected by convenience sampling.  Participants responded to Meaning in Life Questionnaire (MLQ; Steger, Frazier, Oishi, & Kaler), Connor-Davidson Resilience Scale (CD-RISC), Five Facet Mindfulness Questionnaire (FFMQ; Baer, R.‌A., Smith,‌G.‌T.,‌Hopkins,‌J.,‌Krietemeyer,‌J.,‌&‌ Toney) and Diener Flourishing Scale. The results were analyzed by structural equation modeling. The results showed that meaning in life and mindfulness had direct effects on the resilience. Resilience also had direct effects on the flourishing. Moreover the meaning in life and mindfulness showed indirect effect on flourishing by mediational effects of resilience. In general, hypothetical model showed good fit. These findings can be endorsed the importance of the positive role of meaning in life, mindfulness and resilience on the flourishing.